Philosophy and Theology Facing Transhumanism: A Hermeneutic Analysis - Reyes, Johan Méndez; Medina, Ana Padrón; Villacis, Víctor Iza (Journal of Posthumanism, 2025)
Transhumanism holds that human beings possess the ability to create a new identity, redefine their place in the world, reconfigure their relationships with others, and rethink their notion of transcendence. Its foundation lies in the idea that individuals can shape their own destiny and develop new beliefs and narratives. Within this framework, this research aims to analyze philosophy and theology in relation to transhumanism from a hermeneutic perspective. To achieve this, a qualitative methodology is employed, specifically the hermeneutic method and design, which allows for the interpretation of texts within their context. The study concludes that transhumanism, despite its aspiration to build a perfect society, has failed to address humanity’s true needs, such as poverty, violence, disease, and the depletion of natural resources, among others. Rather, there is a growing trend of narcissistic and arrogant individualism among political, scientific, and economic leaders. In this context, posthuman society has yet to provide effective solutions to these global challenges. Therefore, this study seeks to open new pathways for philosophical and theological dialogue, fostering a deeper debate on the meaning and destiny of human beings in the technoscientific era.